FAKTOR YANG MEMENGARUHI TINGGINYA PENYAKIT ISPA PADA BALITA DI PUSKESMAS DELENG POKHKISEN KABUPATEN ACEH TENGGARA - Rahman Sabri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2019)
Acute Respiratory Infection (ARI) is one of the most infectious diseases and causes of death in children in developing countries. This type of research is an analytical survey method with cross sectional approach with the aim to find out the factors that influence the high ARI in infants with the study population as many as 218 mothers of toddlers and samples taken by random sampling are 69 people. The results showed that knowledge had sig-p 0.016 <0.05, sig-p attitude 0.610> 0.05, exclusive breastfeeding sig-p 0.004 <0.05, ventilation sig-p 0.040 <0.05 and dwelling density of sig -p 0.014 <0.05. The conclusion is the influence of knowledge, exclusive breastfeeding, ventilation and density of occupancy of the high ARI in toddlers, while the attitude has no influence on the high ARI in toddlers. It is hoped that this research can be used as a source of explanations and input for the Deleng Pokhkisen Health Center to improve information provision to mothers and the community in the form of counseling or health promotion. Keywords : Influencing Factors, High ARI Disease